Supplier capacity and key account management performance: a stochastic frontier analysis - Ahmmed, Kawsar; Baten, Md Azizul; Hossain, Md Kamrul; Mohd Noor, Nor Azila (Instituto de Economía Aplicada a la Empresa (Universidad del País Vasco UPV/EHU), 2018)
Taking the influences of operational, organizational and relational factors on key account management performance into account, present research examines the antecedent variables of key account management performance. Using a questionnaire, data from 112 ready-made garments companies in Bangladesh were used to evaluate Capacity Oriented Key Account Management Performance through Stochastic Frontier Model. Results show that in the case of medium key account serving capacity, log-likelihood estimation of Maximum Likelihood Estimation (MLE) is found same as the Ordinary Least Square (OLS) estimation whereas for both high and low key account serving capacity, MLE is found better than OLS estimation. It is observed that perceived risks of serving key account, supplier relational investment, and relational intimacy are significant in case of both MLE and OLS estimation methods while in case of MLE team effort and supplier relational investment are recorded significant for the high, medium and low key account serving capacity oriented performance of Banglades hi ready-made garments companies. Again, most of the companies with high key account serving capacity are found showing above average performance, the performance of the companies with medium key account serving capacity is homogeneous. On the other hand, the performance of low key account serving capacity garments companies are more volatile than garments companies with medium and high key account serving capacity. Implications, limitations, and further research options are suggested.